The Effect of Chlorophyll Concentration from Papaya Leaves on the Performance of Dye Sensitized Solar Cell - Rizali, Dede; Suryanto, Heru; Sukarni, Sukarni (Universitas Negeri Malang, 2019)
Dye-Sensitized Solar Cell (DSSC) is the third generation solar cell that has sandwich structure consisted of organic dye material and other components such as titanium dioxide (TiO2) semiconductor, electrolyte, and substrates (counter electrode and working electrode). The dye in the device was made from green plant chlorophyll such as papaya. This research aimed to find the influence of dye concentration from papaya leaves chlorophyll on the performance of DSCC. The discussion covered the output power (Pout), Fill Factor (FF), and efficiency (ɳ). The method in this research was explorative experimental with independent variables such as direct and indirect sunlight. The dependent variables were output power (Pout), Fill Factor (FF), and efficiency (ɳ) from the DSSC. The procedures in this research consisted of substrates preparation, TiO2 paste production, dye solution preparation, electrolyte preparation, counter electrode preparation, and DSSC assembly. The tests on chlorophyll concentration were conducted using spectrophotometry method while the DSSC performance test used 1,000 W/cm2 halogen lamp. The results showed that 100% chlorophyll concentration resulted in 3.1295 mg/m3 chlorophyll content type a. The best DSSC performance was obtained by the DSSC sample that had 100% chlorophyll concentration and 1.1294 mg/m3 chlorophyll content. The direct light of DSSC achieved Pout of 0.9557 mW, FF of 0.07282, and efficiency of 1.499137%. The DSSC with indirect light obtained Pout of 0.00455 mW, FF of 0.01535, and efficiency of 0.049863%.